Coleridge and the Romantic Newspaper The 'Morning Post' and the Road to 'Dejection' - Thomson, Heidi; SpringerLink (Online service) (Cham : Springer International Publishing(Imprint)), 2016)
This book examines how Coleridge staged his private woes in the public space of the newspaper by looking at his publications in the Morning Post, which first published one of his most famous poems, Dejection. An Ode. It reveals how he found a socially sanctioned public outlet for poetic disappointments and personal frustrations which he could not possibly articulate in any other way. Featuring fresh, contextual readings of established major poems; original readings of epigrams, sentimental ballads, and translations; analyses of political and human-interest stories, this book reveals the remarkable extent to which Coleridge used the public medium of the newspaper to divulge his complex and ambivalent private emotions about his marriage, his relationship with the Wordsworths and the Hutchinsons, and the effect of these dynamics on his own poetry and poetics.
1. Introduction: A Character in the Antithetical Manner -- 2. The Return from Germany -- 3. The Morning Post and Introduction to the Tale of the Dark Ladie -- 4. Mothers, Sons, and Poets in the Morning Post -- 5. Homeless at Grieta Hall -- 6. The 1800 Lyrical Ballads, Mary Robinson, and The Mad Monk -- 7. Mary Robinson and the Poet Coleridge -- 8. 'Merely the Emptying out of my Desk' -- 9. Conclusion: Dejection. An Ode in the Morning Post as a Palimpsest -- Notes -- Bibliography -- Index.-.
Keywords: Literature, Modern-18th century; Literature, Modern-19th century; POETRY